Acute effects of exercise on mood in female students - Mamat, Noor Hapizah (Universiti Sains Malaysia, 2009)
The present study was about the acute effects of aerobic dance exercise on mood changes in female university students. It is a field study that involved volunteers who joint the aerobic dance exercise class. Based on previous research, subjects should show positive mental health (an increase in vigor and a decrease in all negative mood subscales; anger, tension, depression, confusion and fatigue) after the exercise. Participants were 16 female students (21.75 ± 0.71 years). They completed the Brunei of Mood Scale (BRUMS) 15 minutes before and immediately after exercise. The aerobic dance exercise session lasted for about 60 minutes including the warm-up, main session and cool-down. The results indicated that the negatives mood subscales of anger (1.88 versus 1.19), tension (0.94 versus 0.44), depression (2.13 versus 0.94), confusion (1.63 versus 0.25) and fatigue (4.19 versus 3.81) were lower, while vigor (positive mood) was higher (7.88 versus 9.81) after the exercise session. However, the changes were only statistically significant for vigor (p = 0.016, eta2 = 0.328) and confusion (p = 0.040, eta2 = 0.252). On the other hand, the results also resembled the Iceberg Profile and may be classified as positive mental health. Findings lend support to the notion that the exercis~ is ~~sociated with ' ~ improved mood. Thus, the aerobic dance exercise can be V,S~d to maintain and regulate positive mental health.